Curcumin for Quality of Life of Multiple Myeloma Patients: a Randomized, Placebo-Controlled Trial: Curcumin for Quality of Life of Multiple Myeloma Patients: a Randomized, Placebo-Controlled Trial - Hendrawati, Anindita Rosenda Eka; Santosa, Damai; Dharminto, Dharminto; Suharti, Catharina (RSUP Dr. Kariadi, 2022)
Background : The main goal of multiple myeloma (MM) therapy is to control the disease, prolong the survival, and improve the life quality. Curcumin affects pro-inflammatory cytokines. There is no research yet that has been conducted to evaluate the effects of curcumin on increasing MM patient's life quality. Objective of this study is to evaluate the effect of curcumin on increasing MM patients' life quality. Methods : Of 24 MM patients were enrolled and were divided randomly into treatment groups (n=12) and controls (n=12). Patients in treatment group received melphalan 4 mg/m2, prednisone 40 mg/m2 (MP) for 7 days and curcumin 8 grams/day for 28 days. The control group received MP and placebo. Quality of life (QoL) scores were measured in early diagnosis and after 4 cycles of treatment. The difference between two groups was analyzed using Mann-Whitney U-Test or Independent T Test. Results : The role function score of the treatment group was better than control. There is a significant difference function score of patients between the treatment and control group, at baseline and 4 cycles treatment (41.66 ± 3.85 vs. 23.61 ± 3.36; 95.83 ± 1.03 vs 76.39 ± 2.51; p=0.022). There was significantly different of insomnia score between treatment and control goup at baseline and the end 4 cycles (41.67 ± 3.79 vs 58.33 ± 3.51; 9.72 ± 1.5 vs 25 ± 1.32; p=0.02). Conclusion : The addition of curcumin in myeloma patients enhances the QoL score, role function score and lowered symptom insomnia.